1984
DOI: 10.1038/312376a0
|View full text |Cite
|
Sign up to set email alerts
|

A developmental gene product of Bacillus subtilis homologous to the sigma factor of Escherichia coli

Abstract: Sporulation of Bacillus subtilis involves sequential morphological and biochemical changes and is regulated by specific genes (spo genes) estimated to occupy more than 30 loci. A mutation in any one of these genes blocks the sporulation process at the corresponding developmental stage. Despite intensive genetic studies, the nature and function of the spo gene products remain unknown. Vegetative B. subtilis RNA polymerase core enzyme may interact with several sigma factors and discriminate among different class… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
88
2

Year Published

1986
1986
2010
2010

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 96 publications
(90 citation statements)
references
References 24 publications
0
88
2
Order By: Relevance
“…In their recent article, Errington et al [2] identify in the previously published sequence of the B. subtilis spoIIAC gene [3] a region exhibiting homology with known sigma factors. This region corresponds to the internal domain conserved in bacterial sigma factors [l] which was also the first one to be noticed in the SpoIIG sequence [4]. However, no homology can be found in the carboxy-terminal region of the spoIIAC product with the postulated DNAbinding domain of the other sigma factors, a serious discrepancy with our model.…”
contrasting
confidence: 54%
“…In their recent article, Errington et al [2] identify in the previously published sequence of the B. subtilis spoIIAC gene [3] a region exhibiting homology with known sigma factors. This region corresponds to the internal domain conserved in bacterial sigma factors [l] which was also the first one to be noticed in the SpoIIG sequence [4]. However, no homology can be found in the carboxy-terminal region of the spoIIAC product with the postulated DNAbinding domain of the other sigma factors, a serious discrepancy with our model.…”
contrasting
confidence: 54%
“…The anti-E antiserum also detected a slightly larger protein, called P31, that was synthesized earlier than and thought to be a precursor of E (292). A combination of genetic and protein analysis revealed that E and P31 (now called pro-E ) were the products of the spoIIG locus (279,292). Pulse-chase and microsequencing experiments revealed that pro-E was processed into E by proteolytic removal of 27 residues from its N terminus (159,278).…”
Section: Activation Of Ementioning
confidence: 99%
“…Nevertheless, there is growing support for the proposal (14-16, 41) that the mother cell-specific counterpart of (rF is cr-, the product of spoIIGB, the second cistron of the spoIIG operon (75,82). The or-protein is synthesized initially as an inactive precursor, pro-a', which is believed to be processed proteolytically by SpoIIGA to yield the active form of the protein (6,30,37,74).…”
mentioning
confidence: 99%